Coping mechanisms of Filipino abused women - Mateo, Judilyn Cruz; Malicdem, Eleanor A. (2009.)
This study was conducted to determine the physical, psychological and sexual coping mechanisms of women after surviving abusive experiences. The concepts of a family or family relationship of the respondents after the abusive experiences were also considered. Respondents were chosen using non-probability purposive sampling. Five abused females with ages 21 to 70 years old were obtained from referrals of friends and relatives in NuevaEcija. Data was gathered through a survey questionnaire. It comprised of four parts including a combined checklist and fill-in type questions. These information were solicited from the respondent's profile; physical, psychological and sexual abusive experiences; coping mechanisms; and perceived concepts of a family or family relationships. Data were analyzed using frequency, ranking and content analysis. Findings of this study showed different coping mechanisms of abused women. These include: participation in religious activities, counseling, seeking legal assistance, moral and emotional support from relatives and friends, participation in socio-civic organizations and alcoholism. The perceived concept of a family by the respondents changed due to their abusive experiences. Separation from spouse and moving out of the house were the initial behaviors of the abused women after the abusive experiences.
Thesis (BS Home Economics)--University of the Philippines Diliman.
Keywords: Abused women -- Philippines